PS7:136 Apoptotic effect of blys on endothelial cells and endothelial progenitor cells is mediated by blys receptors and is reverted by belimumab. (21st March 2018) - Spinelli, FR; Barbati, C; Ceccarelli, F; Colasanti, T; Massaro, L; Morello, F; Garufi, C; Alessandri, C; Valesini, G; Conti, F
Abstract : Circulating endothelial progenitor cells (EPCs) are markers of endothelial function; their reduction and functional impairment in patients with Systemic Lupus Erythematosus (SLE), partially account for endothelial dysfunction. In murine models of atherosclerosis, treatment with a B Lymphocyte Stimulator (BLyS) reduced atherosclerotic plaque size and progression. In a case study on SLE 20 women, our group confirmed a decrease in the number of EPCs, with a significant increase after treatment with Belimumab (BLM). The aims of this study were: to evaluate the ex vivo and in vitro effects of BLyS stimulation and inhibition on the EPC colonies and on endothelial cells; to investigate BLyS receptor expression of on EPCs and endothelial cells. EPCs were isolated from peripheral blood mononuclear cells and defined as CD34+/VEGF-R2 +double positive cells. To evaluate the ability to form colonies, the EPCs of 2 SLE patients and 2 healthy controls were cultured on fibronectin-coated dishes and incubated with BlyS or Blys and BLM and counted after 7 days. Apoptosis of EPCs and endothelial cell line (EA.hy926) was evaluated after 6, 12 and 24 hours incubation with BLyS and after 6 hour with BLyS and BLM. EPC and EA.hy926 were also incubated with anti-B activating factor-receptor (BAFF-R) antibodies, B-cell maturation antigen (BCMA) and transmembrane activator and calcium modulator and cyclophilin ligand (CAML) interactor (TACI), then analysed by cytofluorimetry. The number of EPC colonies in patients was lower than in controls; moreover, colonies were poorly organised compared to controls; BLM incubation restored the structure of the colonies. After 6 hours of incubation, BLyS (20 ng/ml) induced apoptosis of EPC and EA.hy926; co-incubation with BLM inhibited the apoptotic effect. Both EPCs and EA.hy926 expressed BAFF-R (MFI=3.8 and 1.5 respectively) and BCMA (MFI=1.25 and 1.15); EPCs also express TACI (MFI=1.4). The results of this study showed: a quantitative and qualitative alteration of colonies in patients, restored after ex vivo and in vitro BLM treatment; the apoptotic effect of BLyS on EPC and endothelial cells inhibit by BLM and the preferential expression of BAFF–R on the surface of EPC and EA.hy926.